Cochlear implants in the social courts - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: Since the indication for receiving a cochlear implant (CI) has widened (single-sided deafness [SSD], electric acoustic stimulation [EAS], bilateral CI, CI for long-term deafness), more and more patients come into consideration for such a treatment. Hence, disputes increasingly arise between patients and their insurance companies concerning the question of whether surgery and follow-up treatment have to be paid for by statutory health insurance. OBJECTIVE: This work provides an overview of judgments rendered by the German social courts. We investigated whether and in which cases it is advisable for a patient to go to court, and how long the proceedings may take. MATERIALS AND METHODS: We looked for judgments in the two biggest commercial legal databases and in the database of the German social courts, using combinations of the search parameters "Cochlear," "Cochlea," "Implant," and "Implantat." Three verdicts were attained by directly contacting the court; another one was mentioned in an article. The reviewed judgements were issued between 2003 and 2017. RESULTS: A total of 12 judgments were found. The patients won in all but one of the main proceedings. The case that was lost concerned exceptional circumstances. One patient didn't get the desired interim measure, but won in the main proceedings. The proceedings took between 1 year and 8 months, and 9 years and 5 months. CONCLUSION: Despite the amount of time the patient has to invest, taking legal action is worthwhile. The proceedings at the social courts are generally exempt from charges. In most cases, the statutory health insurance is ordered to pay for a CI.
EVALuna2:33194

Hearing aid provision - can the limited obligation of statutory health insurance to provide indemnification only up to the reference price be successfully challenged in the social courts in cases of medical indication? - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2019)
OBJECTIVE: When patients are provided with hearing aids, the question may arise whether they are entitled to technically advanced and therefore more expensive hearing aids in cases of medical indication, or just to hearing aids for the reference price. This work provides an overview of decisions rendered by the German social courts. We investigated whether it is advisable for a patient to go to court if the statutory health insurance has disputed a claim, and how long the proceedings may take. MATERIAL AND METHODS: We looked for decisions in the commercial legal database "juris", using the search parameters "Hörgerät" (hearing aid) and "Zuzahlung" (additional payment). The reviewed decisions were issued between 2009 and 2019. RESULTS: A total of 97 relevant decisions were found. The results varied according to the specifics of the individual case. 63 % of the patients won their cases. The court procedures took between 0.3 years and 10.4 years. CONCLUSIONS: The study shows that it is uncertain whether the costs for hearing aids that exceed the reference price will be covered or reimbursed. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory health insurances or other providers refuse to meet expenses incurred despite indication.
EVALuna2:209866

Hörgeräteversorgung – Kann die Begrenzung der Leistungspflicht der Krankenkassen durch Festbeträge bei medizinischer Indikation erfolgreich vor den Sozialgerichten angefochten werden? - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2019)
OBJECTIVE: When patients are provided with hearing aids, the question may arise whether they are entitled to technically advanced and therefore more expensive hearing aids in cases of medical indication, or just to hearing aids for the reference price. This work provides an overview of decisions rendered by the German social courts. We investigated whether it is advisable for a patient to go to court if the statutory health insurance has disputed a claim, and how long the proceedings may take. MATERIAL AND METHODS: We looked for decisions in the commercial legal database "juris", using the search parameters "Hörgerät" (hearing aid) and "Zuzahlung" (additional payment). The reviewed decisions were issued between 2009 and 2019. RESULTS: A total of 97 relevant decisions were found. The results varied according to the specifics of the individual case. 63 % of the patients won their cases. The court procedures took between 0.3 years and 10.4 years. CONCLUSIONS: The study shows that it is uncertain whether the costs for hearing aids that exceed the reference price will be covered or reimbursed. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory health insurances or other providers refuse to meet expenses incurred despite indication.
CRIS-Team Scopus Importer:2019-10-22

Postoperative legal disputes involving patients with cochlear implants - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (HNO, 2018)
BACKGROUND: After the implantation of one or two cochlear implants additional problems often arise concerning the question which further costs have to be covered by statutory insurances or other insurance providers, e.g. within the framework of integration aid. OBJECTIVE: This article provides an overview of judgments rendered by the German social courts. It was investigated whether and in which cases it is advisable for a patient to go to court, and how long the proceedings may take. MATERIAL AND METHODS: A search was made for judgments in the two biggest commercial legal databases and in the database of the German social courts, using combinations of the search parameters "Cochlear", "Cochlea", "Implant", and "Implantat". The reviewed judgments were issued between 2002 and 2017. RESULTS: A total of 13 judgments were found. The results varied according to the specifics of the individual case and 54% of the patients won their cases. The court procedures took between 2 months (starting from the filing of a complaint, date of application in this case unknown), and 6 years and 11 months. CONCLUSION: This study showed that it is uncertain whether costs that are not caused directly by the surgery or the postoperative treatment will be remunerated. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory insurances or other providers refuse to meet expenses incurred.
EVALuna2:35385